Synthesis of spiro[dihydropyridine-oxindoles] via three-component reaction of arylamine, isatin and cyclopentane-1,3-dione - Yan Sun; Jing Sun; Chao-Guo Yan (Beilstein Journal of Organic Chemistry, 2013)
A fast and convenient protocol for the synthesis of novel spiro[dihydropyridine-oxindole] derivatives in satisfactory yields was developed by the three-component reactions of arylamine, isatin and cyclopentane-1,3-dione in acetic acid at room temperature. On the other hand the condensation of isatin with two equivalents of cyclopentane-1,3-dione gave 3,3-bis(2-hydroxy-5-oxo-cyclopent-1-enyl)oxindole in high yields. The reaction mechanism and substrate scope of this novel reaction is briefly discussed.